Transport of basic amino acids by membrane vesicles of Lactococcus lactis. - Driessen, A J (1989)
The uptake of the basic amino acids arginine, ornithine, and lysine was studied in membrane vesicles derived from cells of Lactococcus lactis which were fused with liposomes in which beef heart mitochondrial cytochrome c oxidase was incorporated as a proton motive force (PMF)-generating system. In the presence of ascorbate N,N,N'N'-tetramethylphenylenediamine-cytochrome c as the electron donor, these fused membranes accumulated lysine but not ornithine or arginine under aerobic conditions. The mechanism of energy coupling to lysine transport was examined in membrane vesicles of L. lactis subsp. cremoris upon imposition of an artificial electrical potential (delta psi) or pH gradient or both and in fused membranes of these vesicles with cytochrome c oxidase liposomes in which the delta psi and delta pH were manipulated with ionophores. Lysine uptake was shown to be coupled to the PMF and especially to the delta psi, suggesting a proton symport mechanism. The lysine carrier appeared to be specific for L and D isomers of amino acids with a guanidine or NH2 group at the C6 position of the side chain. Uptake of lysine was blocked by p-chloromercuribenzene sulfonic acid but not by maleimides. Counterflow of lysine could not be detected in L. lactis subsp. cremoris, but in the arginine-ornithine antiporter-containing L. lactis subsp. lactis, rapid counterflow occurred. Homologous exchange of lysine and heterologous exchange of arginine and lysine were mediated by this antiporter. PMF-driven lysine transport in these membranes was noncompetitively inhibited by arginine, whereas the uptake of arginine was enhanced by lysine. These observations are compatible with a model in which circulation of lysine via the lysine carrier and the arginine-ornithine antiporter leads to accumulation of arginine.